British Thoracic Society quality standards for the investigation and management of pulmonary nodules. Issue 1 (16th April 2018) - Baldwin, David; Callister, Matthew; Akram, Ahsan; Cane, Paul; Draffan, Jeanette; Franks, Kevin; Gleeson, Fergus; Graham, Richard; Malhotra, Puneet; Pearson, Philip; Subesinghe, Manil; Waller, David; et al.
Abstract : Introduction: The purpose of the quality standards document is to provide healthcare professionals, commissioners, service providers and patients with a guide to standards of care that should be met for the investigation and management of pulmonary nodules in the UK, together with measurable markers of good practice. Methods: Development of British Thoracic Society (BTS) Quality Standards follows the BTS process of quality standard production based on the National Institute for Health and Care Excellence process manual for the development of quality standards. Results: 7 quality statements have been developed, each describing a key marker of high-quality, cost-effective care for the investigation and management of pulmonary nodules, and each statement is supported by quality measures that aim to improve the structure, process and outcomes of healthcare. Discussion: BTS Quality Standards for the investigation and management of pulmonary nodules form a key part of the range of supporting materials that the Society produces to assist in the dissemination and implementation of guideline recommendations.